2016
DOI: 10.1111/evj.12610
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological survey on the prevalence of equine peripheral dental caries in the United Kingdom and possible risk factors for its development

Abstract: Peripheral caries is common in British horses, primarily affecting the caudal cheek teeth. There was limited evidence of an association between feeding and PC. The association between PC and concurrent dental disorders indicates that these should be addressed in affected horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(73 citation statements)
references
References 18 publications
3
64
3
2
Order By: Relevance
“…Similarly to other studies , the present study found the prevalence of caries to be much higher in the caudal teeth, with the Triadan 9–11s most likely to be affected. As the feed moves caudally in the mouth, it is broken down into smaller particles and becomes more saturated by saliva, which makes the WSCs more accessible to bacteria, as well as moist and hence ‘sticky’ enough to be able to adhere to the teeth.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly to other studies , the present study found the prevalence of caries to be much higher in the caudal teeth, with the Triadan 9–11s most likely to be affected. As the feed moves caudally in the mouth, it is broken down into smaller particles and becomes more saturated by saliva, which makes the WSCs more accessible to bacteria, as well as moist and hence ‘sticky’ enough to be able to adhere to the teeth.…”
Section: Discussionsupporting
confidence: 87%
“…That high concentrate and silage diets are likely to cause peripheral caries has been the subject of frequent discussion and a recent Edinburgh‐based study found a limited association with the feeding of moderate levels of concentrate feed . This was not the case in the present study sample, in which the main dietary factor relating to the development of peripheral caries concerned the choice of hay fed to the horse.…”
Section: Discussioncontrasting
confidence: 65%
“…In this study 71.4% (45/63) of the population examined (all cases referred for dental examination/treatment) were affected by PC. This prevalence is higher than the 51.7% reported in a recent UK‐wide survey , which is likely due to the high prevalence of concurrent dental problems in the current hospital referral population, which is a risk factor for PC . There was no statistically significant difference in diversity within‐sample when the PC group and control group were compared.…”
Section: Discussioncontrasting
confidence: 60%
“…Borkent et al . () found a prevalence of 51% in UK‐wide clinical survey, where most oral examinations were performed using a headlight and dental mirror, a technique that is likely to be less sensitive than oral endoscopy. Although post‐mortem examination allows the most detailed dental examination, this factor could not fully explain the very high PC prevalence (91%) found in this study, because PC lesions, especially on the palatal aspect of maxillary CT, even of the caudal three CT, would readily be detected during a competent oral examination using a dental mirror or endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…; Borkent et al . ) have shown PC to most commonly affect the caudal three cheek teeth (CT; Triadan 09s, 10s and 11s) indicating that a more cariogenic environment is present in the caudal aspect of the oral cavities of affected horses.…”
Section: Introductionmentioning
confidence: 99%